2023
DOI: 10.1002/jmv.28734
|View full text |Cite
|
Sign up to set email alerts
|

Association of gut microbiota with COVID‐19 susceptibility and severity: A two‐sample Mendelian randomization study

Abstract: Evidence supports the observational associations of gut microbiota with the risk of COVID-19; however, it is unclear whether these associations reflect a causal relationship. This study investigated the association of gut microbiota with COVID-19 susceptibility and severity. Data were obtained from a large-scale gut microbiota data set (n = 18 340) and the COVID-19 Host Genetics Initiative (n = 2 942 817). Causal effects were estimated with inverse variance weighted (IVW), MR-Egger, and weighted median, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Intestinal barrier impairment, dysbiosis of gut microbiota, and perturbation of metabolites are prevalent occurrences among individuals with COVID‐19. Extensive research has consistently shown the association between microbiota composition and the morbidity, exacerbation, and mortality rates seen in COVID‐19 patients 51–55 . The gut microbiota facilitates the assessment of sickness severity in individuals with COVID‐19 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal barrier impairment, dysbiosis of gut microbiota, and perturbation of metabolites are prevalent occurrences among individuals with COVID‐19. Extensive research has consistently shown the association between microbiota composition and the morbidity, exacerbation, and mortality rates seen in COVID‐19 patients 51–55 . The gut microbiota facilitates the assessment of sickness severity in individuals with COVID‐19 56 .…”
Section: Discussionmentioning
confidence: 99%
“…patients. [51][52][53][54][55] The gut microbiota facilitates the assessment of sickness severity in individuals with COVID-19. 56 From a mechanical standpoint, it is observed that COVID-19 disrupts the composition of gut microbiota and metabolites.…”
Section: Potential Confounding Factors and Mechanismsmentioning
confidence: 99%
“…We set the following steps to screen the best IVs to ensure the robustness of our study; first, screening of significantly relevant SNPs from gut microbiome GWAS data as IVs. However there is a problem that is prevalent in MR studies of the gut microbiota 19 , 23 . If the number of SNPs obtained by using the genome-wide statistical significance threshold ( p <5×10-8) is few, it may lead to biased results.…”
Section: Methodsmentioning
confidence: 99%
“… 26 Third, removal of palindromic SNPs with A/T or G/C structures from SNPs obtained in the second step. 19 , 26 Finally, we calculated the F statistic to detect the strength of the correlation between the SNPs obtained in the third step and the exposure, removing SNPs with weak instrumental bias ( F values <10). 27 …”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that the gut microbiota may have a causal relationship with the severity of COVID‐19, thus providing new evidence and ideas for the study of the pathogenesis of SARS‐CoV‐2 mediated by gut microbiota. 107 , 108 …”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%